PENTINGNYA IMPLEMENTASI PENDIDIKAN KARAKTER SISWA DI KELAS VI SDN 14 KOTO BARU DALAM MATA PELAJARAN PANCASILA - Rizkia Zahra Jannah; Fani Anggelia (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dharmas Indonesia, 2025)
Abstract: The character of students is formed through the application of character education in the Pancasila subject. However, in practice, there is still little universal explanation regarding the efforts to foster and develop students' character in the context of Pancasila education. This research aims to understand the implementation of character education in the Pancasila subject in grade VI of SDN 14 Koto Baru, as well as to identify the challenges faced during the implementation stages. The method used in this research is qualitative, with respondents consisting of teachers and students. Data collection was conducted through observation, interviews, and documentation. The data processing process includes data reduction, data presentation, and verification. The research results show that the programs prepared by the teachers are used as guidelines in carrying out learning and instilling character values. The challenges faced in implementation include the misalignment between the school programs that have been applied and the living environment of the students. Thus, it can be concluded that the implementation of character education in the subject of Pancasila education at SDN 14 Koto Baru has been well carried out.